Chimpanzee adenoviral vector prime-boost regimen elicits potent immune responses against Ebola virus in mice and rhesus macaques - Xi Yang; Xiang Wang; Yufeng Song; Ping Zhou; Dapeng Li; Chao Zhang; Xia Jin; Zhong Huang; Dongming Zhou (Emerging Microbes and Infections)
In the last few decades, Ebola virus (EBOV) has emerged periodically and infected people in Africa, resulting in an extremely high mortality rate. With no available prophylaxis or cure so far, a highly effective Ebola vaccine is urgently needed. In this study, we developed a novel chimpanzee adenovirus-based prime-boost vaccine by exploiting two recombinant replication-deficient chimpanzee adenoviral vectors, AdC7 and AdC68, which express glycoproteins (GP) of the EBOV strain identified in the 2014 outbreak. Our results indicated that a single immunization using AdC7 or AdC68 could stimulate potent EBOV-specific antibody responses, whereas the AdC7 prime-AdC68 boost regimen induced much stronger and sustained humoral and cellular immune responses in both mice and rhesus monkeys, compared with AdC7 or AdC68 single vaccination or the AdC68 prime-AdC7 boost regimen. This prime-boost vaccine could also protect mice from the simulated infection with EBOV-like particle (EBOVLP) in biosafety level 2 (BSL-2) laboratories, and antibodies from the prime-boost immunized rhesus macaques could passively provide protection against EBOVLP infection. Altogether, our results show that the AdC7 prime-AdC68 boost vaccine is a promising candidate for further development to combat EBOV infections.